BONE DISEASES AVASCULAR NECROSIS, OSTEOMYELITIS, METHODS OF STRENGTHENING BONE EROSION - Onorboyev Yorkinbek Zarovich; Jurayev Jakhongir Alisherovich; Asanadilova Aknur Bakhtbekovna; Bakhronova Sevinch Uralovna; Kubayev. A. E (International Journal on Human-Computing Studies, 2023)
This article describes the methods of natural treatment of types of bone erosion. Methods of using natural medicinal plants in the treatment process are shown.